2010
DOI: 10.4257/oeco.2010.1403.04
|View full text |Cite
|
Sign up to set email alerts
|

Dengue and Land Cover Heterogeneity in Rio De Janeiro

Abstract: Dengue epidemics in Brazil have become more frequent and more severe and involving larger populations in the last years. In Brazil Aedes aegypti is the only known vector. During the 2007-2008 period, Rio de Janeiro state experienced the most severe dengue epidemics ever reported in terms of morbidity and mortality. During this period, 322,371 cases and 240 deaths were registered, with 100 deaths due to dengue haemorragic fever/ dengue shock syndrome and 140 due to other dengue-related complications. Dengue tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…The city of Rio de Janeiro is characterized by great spatial heterogeneity and complexity. The city has a high population density, disorderly urban growth, lack of infrastructure, environmental degradation, and major socio-spatial inequality 18,19 . These territorial characteristics together with the local climate conditions contribute to establishing and maintaining the epidemics, hindering dengue control and prevention measures 20,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…The city of Rio de Janeiro is characterized by great spatial heterogeneity and complexity. The city has a high population density, disorderly urban growth, lack of infrastructure, environmental degradation, and major socio-spatial inequality 18,19 . These territorial characteristics together with the local climate conditions contribute to establishing and maintaining the epidemics, hindering dengue control and prevention measures 20,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study of successive dengue epidemics in Rio de Janeiro that occurred in 2007 and 2008, Rosa-Freitas et. al demonstrated that dengue incidence positively correlated with neighborhoods ( bairros ) with a larger proportion of their land area composed of urban slums [5]. In Singapore in the late 1960s, the fraction of houses that tested positive for Aedes mosquito breeding was highest in the city's slums and in those with greatest population density.…”
mentioning
confidence: 99%
“…Located in the southeastern region of the country, it has an area of approximately 1197 km 2 and a population of 6,320,446 inhabitants in 2010 [24]. It has significant spatial heterogeneity generated by the process of urban land use and occupation, and its peculiar physiographic characteristics, making this city a mosaic of contrasting urban and environmental landscapes [25,26]. It is politically divided into 160 neighborhoods and 33 administrative regions (Figure 1).…”
Section: Study Areamentioning
confidence: 99%